Tinjauan Yuridis Terhadap Putusan Lepas Dari Segala Tuntutan Hukum (Onstlag Van Rechtsverloging) Pada Tindak Pidana Korupsi: Studi Terhadap Putusan Pengadilan Negeri No 56/Pid.Sus.Tpk/2017/P.n.Kpg - Yohana Oktavia Ngode Lagho; Karolus K.Medan; Orpa G.Manuain (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In criminal cases, particularly corruption cases, judges have the absolute authority and duty to decide and follow up on these matters. The background of this writing is that corruption is an extraordinary crime that hinders national development and must be prosecuted according to applicable regulations. The issue with this decision is that the judges were not meticulous enough, as they acquitted the defendant despite the defendant's actions causing state losses. An acquittal (Onslag Van Vervolging) means that the suspect or defendant in a corruption case is not subjected to any punishment or sanction.The analysis focuses on the verdict No. 56/Pid.Sus-Tpk/2017/Pn.Kpg, highlighting specific details that deserve further scrutiny. The juridical analysis of this decision will address the formulated issues, namely the basis for the judge's consideration in issuing an acquittal and how the judge should have ruled. The judge's considerations encompass three aspects: Philosophical, Juridical, and Sociological. This juridical analysis will include an understanding of the arguments presented, the legal basis used, and the factors influencing the court's decision to acquit the defendant of all charges. Therefore, in ruling on this case, the judge must ensure the utility aspect so that the defendant is penalized according to the applicable regulations.The method used in this journal is the normative juridical method, employing legislative and conceptual methodologies, providing an analytical perspective on problem-solving from the standpoint of the underlying legal concepts, utilizing data from literature and the internet as sources.Top of FormBottom of Form